2011
DOI: 10.1038/leu.2011.198
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive activation of STAT3 in Sézary syndrome is independent of SHP-1

Abstract: Constitutive and persistent activation of STAT3 has been implicated in the pathogenesis of many malignancies. Studies of CTCL cell lines have previously suggested that aberrant activation of STAT3 is mediated via silencing of the negative regulator SHP-1 by promoter methylation. In this study of ex vivo tumour cell populations from 18 Sé zary syndrome (SS) patients, constitutive phosphorylation of STAT3, JAK1 and JAK2 was present in all patients, but was absent in comparative CD4 þ T-cells from healthy control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 55 publications
2
7
0
1
Order By: Relevance
“…HDAC inhibitors increase global histone acetylation in cancer cells and promote T-cell apoptosis (Zhang et al, 2005;Shao et al, 2010). While studies have begun to identify the molecular basis of the various subtypes of mature T-cell lymphomas (Campbell et al, 2010;Lemonnier et al, 2012;McKenzie et al, 2012;Ferrara et al, 2013;Palomero et al, 2014), responses to romidepsin and belinostat have been reported across the entire disease spectrum, without regard to subtype. The precise mechanism underlying activity against T-cell lymphoma has yet to be determined, and multiple biological effects have been invoked.…”
mentioning
confidence: 99%
“…HDAC inhibitors increase global histone acetylation in cancer cells and promote T-cell apoptosis (Zhang et al, 2005;Shao et al, 2010). While studies have begun to identify the molecular basis of the various subtypes of mature T-cell lymphomas (Campbell et al, 2010;Lemonnier et al, 2012;McKenzie et al, 2012;Ferrara et al, 2013;Palomero et al, 2014), responses to romidepsin and belinostat have been reported across the entire disease spectrum, without regard to subtype. The precise mechanism underlying activity against T-cell lymphoma has yet to be determined, and multiple biological effects have been invoked.…”
mentioning
confidence: 99%
“…Phosphorylation of JAK1 and JAK2, but not activating mutations in these two enzymes, also contributes to the constitutive STAT3 activation, which is independent of downregulation or loss of SHP-1 tyrosine phosphatase. In this respect, the use of JAK inhibitors represents a promising therapeutic option already confirmed by in vitro data (McKenzie et al, 2011).…”
Section: Small-molecule Tyrosine Kinase Inhibitorsmentioning
confidence: 95%
“…HUT-78 cells were electroporated using the Gene Pulser® II Electroporation System (Biorad) at 240V and 975uF with 100 nM of RAD23B-specific (D-011759-04) or scrambled siRNA (D-001206-13-05; both Dharmacon) and cultured for 48 hours as described (Verma et al 2010) . RAD23B depletion was confirmed by immunoblot and by PCR of cDNA using RAD23B-specific primers (5'-TGACCCCGAGGAGACGGTGA-'3; reverse: 5'-GCAGGTGTGGAAGTGGGGGC-'3) and cyclophilin-specific primers as described (McKenzie et al 2012).…”
Section: Sirna Knockdownmentioning
confidence: 99%